P1305 Rare complication of a frequent disease. (17th January 2020) - Boeangiu, S; Stoica, E; Anton, M; Maresiu, C; Margineanu, C; Marin, G; Penes, D; Chioncel, O
Abstract: Introduction: Splenic abcess represents a rare complication of left-sided infective endocarditis. Unlike splenic infarction, which is a more benign condition, splenic abcess requires rapid diagnosis and treatment as its course can be fatal. We present the case of a 52- year old male, with diabetes and hypertension, admitted for shortness of breath and fever in the past two months. Clinical examination revealed respiratory distress, tachypnea, diastolic murmur on the left sternal border. Baseline laboratory investigations showed elevated inflammation markers, leukocytosis and thrombocytosis. Enterococcus faecalis was isolated from the hemocultures. Transthoracic echocardiography revealed a dilated left ventricle (LV), with preserved LV ejection fraction, with severe aortic regurgitation due to valve destruction. A large (11mm diameter) vegetation-like structure attached to the ventricular side of the right coronary cusp, protruding into the left ventricular outflow tract was identified. Further evaluation by transoesopahgeal echocardiography did not identify other lesions, except for secondary moderate mitral regurgitation, with intact mitral leaflets. Dual antibiotic therapy with Ampicilin and Gentamycin was initiated. Surgery was planned after infection control. The first three days were uneventful, with rapid resolution of fever and inflammatory markers, but on the fourth day, the patient developed severe abdominal pain, with its focal point in the left hypochondrium. Contrast abdominal CT was performed and large multiple subcapsular lesions were identified. These findings, correlated with the symptomatology, suggested embolic splenic abcess and infarction. The patient successfully underwent laparoscopic splenectomy, but soon after he developed sepsis with respiratory failure and neurological deterioration (with normal CT scan) and was admitted to the intensive care unit, where he was intubated and mechanically ventilated. Consensus after discussions between cardiology, cardiac surgery and neurology services was to immediately replace the aortic valve, given the inability to otherwise control the infection. Intraoperative images were consistent with perforation of the right coronary cusp. During hospitalization in the ICU following cardiac surgery, the patient was extubated and his neurological function markedly improved. Repeated TTE and TEE showed normal prosthetic valve function and resolution of mitral regurgitation. The patient continued to improve clinically until his discharge. Conclusions: We presented a case of a rare pathogenic entity- splenic abscess and infarction- due to systemic embolization from infective aortic valve endocarditis. Multidisciplinary teamwork was required between cardiologist, intensive care specialist, neurologist, infectionist, general surgeon and cardiac surgeon. Splenectomy was performed before valve replacement, a treatment-course characteristic in the occurrence of these rare cases.